Plato's Dichotomous World as the metaphysical foundation of his theory of the Forms of Government - Silva, Gustavo Javier Castro (2023)
The article aims to analyze the extent to which Plato's metaphysical thought influences the elaboration of his political theory and, in particular, his theory of forms of government. For this reason, the different moments and relevant philosophical elements of the so-called “Allegory of the Cave” will be analyzed, as a paradigmatic example of the justification of the metaphysical dichotomy in Platonic philosophy.